The moderating effect of service types on the relationship between emotional intelligence and organization role / Abdul Kadir Othman, Mohamed Sulaiman and Ali Al-Kahtani - Othman, Abdul Kadir; Sulaiman, Mohamed; Al-Kahtani, Ali (Research Management Institute (RMI), 2011)
Emotional intelligence (EI) is claimed to enhance pro-social behavior, however the claim cannot be generalized to the whole service industry, since services vary significantly. Some services require high levels of customization; while others focus on service standardization. In offering customized services, service providers need to use higher levels of discretion and judgment compared to those offering standardized services. Therefore, this study investigates the moderating effect of service types on the relationship between EI factors (self-emotion appraisal, others emotion appraisal, regulation of emotion and use ofemotion) and service providers' organization role effectiveness. Analysis of J67 responses revealed that there is a significant relationship between self emotional appraisal (SEA) and organization role for moderator-based subgroups. The implication of which is that EI is actively implemented by service providers in mass service to engage in effective organization role.